Global Financial Tightening Conditions and Foreign Exchange Volatility in Kenya - Caspah Lidiema; Twisha Adhikary Chakraborty (European Scientific Journal, ESJ, 2026)
Emerging market economies, such as Kenya, are experiencing heightened foreign exchange (FX) volatility because of ongoing global financial-tightening measures that integrate them into a dysfunctional global economic system. In contrast, theoretical models, such as the Conventional Mundell–Fleming model and post-Keynesian–structuralist theory, diverge on the transmission mechanisms. Therefore, this study tests these competing frameworks to examine the impact of U.S. Federal Reserve (FED) rates, global liquidity (GLI), and global risk factors on Kenya shilling volatility. This study employed a two-stage multivariate volatility dynamic conditional correlation exponential GARCH (DCC-EGARCH) model to measure the impact of financial tightening on Kenya’s Forex volatility from January 2004 to June 2025. The results confirm strong persistence in FX volatility driven by Fed tightening and global risk, with significant DCC correlations rejecting transitory absorption. Domestic monetary policy, proxied by the central bank rate (CBR), exhibits a weak shock response despite high persistence, whereas Fed/CBR and GLI/CBR interactions show procyclical leverage effects, validating Köhler's Minskyan cycles over symmetric Mundell-Fleming adjustments. These findings advance emerging market theoretisation by demonstrating how global financial tightening triggers contractionary balance-sheet channels in debt-dependent economies, thereby limiting domestic monetary policy autonomy. Kenya should prioritize macroprudential buffers alongside reserves accumulation over sole rate reliance to mitigate future US-led volatility spillovers. The originality of this paper lies in the testing of the Conventional Mundell-Fleming model, which views flexible rates as shock absorbers, versus the post-Keynesian-structuralist theory, which warns of endogenous amplification via balance-sheet fragilities.